Developing an Online Marketing Model Suitable for Sun-dried Pork Products of the Sriyothin Thai Pork Enterprise Group Nong Pling Subdistrict Mueang District Kamphaeng Phet Province - donbanthao, anantitra; Sirikitsathian, Chayanan (Lampang Rajabhat University Journal, 2024)
This research aims to: 1) develop an online market for the Sri Yothin Thai Pork Community Enterprise Group in Nong Pling Subdistrict, Mueang District, Kamphaeng Phet Province; 2) test the online market for the Sri Yothin Thai Pork Community Enterprise Group; and 3) analyze the business costs and returns of the Sri Yothin Thai Pork Community Enterprise Group. The population consists of 15 members of the Sri Yothin Thai Pork Community Enterprise Group and 100 consumers of the enterprise’s products in Nong Pling Subdistrict, Mueang District, Kamphaeng Phet Province. Data was collected through interviews and questionnaires. Statistics used for data analysis include percentage, mean, and standard deviation. The study results show that: 1) Posting products on Facebook for promotion or advertising often focuses on creating followers, sales, and using appropriate content can generate interest and increase sales. 2) The overall online market testing of the enterprise group was at a high level (mean = 4.49). 3) Cost analysis consists of 1) raw materials, 2) labor costs, and 3) production expenses. The return analysis for sun-dried pork production includes 1) a profit margin ratio of 43.05%, and 2) a break-even point of 869.69 baht.